KANDUNGAN NILAI MORAL DALAM UNGKAPAN TRADISIONAL JAWA DAN PEPATAH CINA - Sri Harti Widyastuti (Litera, 2013)
This study aims to describe the moral values in Javanese traditional expressions and Chinese proverbs. The data on Javanese expressions were collected from Javanese course books and Kasusastran Jawi and those on Chinese proverbs were collected from Pepatah China Kuno untuk Generasi Modern. The data were analyzed by classifying the themes and comparing Javanese traditional expressions with Chinese proverbs. The findings are as follows. First, the themes include (a) self-control, (b) ethics of marriage and social life, (c) leadership ethics, and (d) ethics of managing a country and nation. Second, the similarity in themes shows a common way of life in Javanese and Chinese societies. This can serve as a means of understanding the cultures of the two ethnic groups so that there is a close relationship and mutual respect.